Assessing The Fairness of Tuition Fee Allocation Using Activity-Based Costing: Evidence from An Indonesian Private Primary School - Rosy Aprieza Puspita Zandra; Nita Roudhotus Saidah; Zainal Abdul Haris (Harmoni Economics: International Journal of Economics and Accounting, 2026)
Tuition fee determination remains a major challenge in educational cost management because many schools apply uniform tuition fee policies despite differences in educational resource consumption among student groups. This study aims to assess the fairness of tuition fee allocation at SD Plus Sunan Pandanaran, Indonesia, using the Activity-Based Costing (ABC) approach. A quantitative case study design was employed using financial and operational data collected through documentation and interviews. The ABC method was implemented by identifying educational activities, establishing cost pools, determining cost drivers, calculating activity rates, and allocating costs according to resource consumption. The findings revealed significant differences in resource utilization between grades 1–2 and grades 3–6, particularly in instructional activities, administrative services, extracurricular programs, and facility usage. The ABC analysis produced monthly tuition fees of IDR 88,984.55 for grades 1–2 and IDR 97,642.35 for grades 3–6, while the school currently applies a uniform fee of IDR 60,000. These results indicate fairness gaps of IDR 28,984.55 and IDR 37,642.35, reflecting implicit cross-subsidization among student groups. The study concludes that Activity-Based Costing provides a more transparent, accurate, and equitable basis for tuition fee allocation while supporting evidence-based financial decision-making in educational institutions.